2001
DOI: 10.1034/j.1399-3046.2001.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus: The good, the bad, and the ugly

Abstract: The aim of this study was to evaluate the efficacy and side‐effects of tacrolimus in pediatric transplant patients previously receiving cyclosporin A (CsA). This study was a retrospective chart review strengthened by a concomitant patient interview. Eleven pediatric cardiac or renal transplant patients, who had been converted from CsA to tacrolimus from October 1995 to January 1999 at The Cleveland Clinic Foundation, were included; there were six renal and five cardiac transplant patients. Each chart was revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…One study reported severe neurotoxicity in one of 14 children undergoing RTPL (7). headache and tremor in two of 11 patients switched over to tacrolimus (17). Another publication described only mild neurologic symptoms, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported severe neurotoxicity in one of 14 children undergoing RTPL (7). headache and tremor in two of 11 patients switched over to tacrolimus (17). Another publication described only mild neurologic symptoms, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Immunosuppressive drugs such as cyclosporine A and tacrolimus seem to act synergistically with EBV as tumor inducing factors [2].…”
mentioning
confidence: 99%
“…Compared with CsA, FK506 is associated with an increased risk for development of PTLD [2,3,5]. Typically, B-lymphocytes are latently infected by EBV and so the virus is hidden from the immune system.…”
Section: Discussionmentioning
confidence: 98%